Mechanical and tribological enhancement of AA6063 aluminum alloy using solid sphere fly ash particles reinforcement - Razzaq, Alaa Mohammed (2018)
Fly ash (FA) has gathered widespread attention as a potential reinforcement for metal matrix composites (MMCs) to enhance the properties and reduce the cost of production. It is the most inexpensive and low density reinforcement available in large quantities as solid waste by-product. Aluminum alloys have been used in various engineering fields, such as automotive and aerospace industries, due to their low density and good mechanical properties. There is need to improve the performance of these alloys by adding reinforcements to extend their usage in many applications under wider service conditions. In this work, efforts are directed to improve the mechanical and tribological properties of AA6063 with solid sphere FA reinforcements. Relevant works were found to focus only on cenosphere FA particulates. There are many fabrication techniques available to manufacture these composites according to matrix and reinforcement materials. The compocasting technique for the fabrication of the AA6063 matrix composite reinforced with FA particles is the focus of this research. FA content, in the range of 0 –12 wt. % in increasing increments of 2% were added to the molten AA6063 alloy until they were completely blended and cooled down just below the liquidus to keep the slurry in the semi-solid state. Afterwards, the molten AA6063-FA composites were cast into prepared cast iron molds. Several techniques were used to evaluate the microstructure properties of these composites. The bulk density, porosity percentage and thermal properties of the composites were tested. This study also investigated the effect of FA addition on the mechanical properties of AA6063-FA composites. The effect of FA addition, applied load and sliding speed on the dry sliding frictional and wear behaviour has been considered in this study. Pin on disc test were conducted at different loads (24.5, 49, and 73.5 N) as well as the various sliding speeds using in this test (150, 200, and 250 rmp.) with a constant period time (10 minutes). The microstructural results showed good distribution of FA particles in the AA6063 matrix with interfacial bonding. The AA6063-FA composites exhibited good mechanical and tribological properties than the unreinforced AA6063 aluminum alloy. The microhardness and the strength significantly increased with increase of FA content. While the impact energy and density decreased with increase in the FA content. The tensile strength of AA6063 alloy increased by 28 % with 10 wt. % of FA, the compression strength improved by 100 % with 10 wt. % of FA. Wear rate decreased with increase of FA content but increased with increase of sliding speed and applied load. The coefficient of friction declined with increase of FA content, sliding speed, and applied load. The findings from the statistical analysis are the order of significance of the design parameters, which revealed the FA content as having the highest influence on the wear rate and coefficient of friction, followed by applied load and sliding speed. Addition to that, the strongest interaction effects is FA content with applied load. The models produced would be a useful tool in the process of AA6063-FA composites design, and can be used as a replacement for the expensive conventional experimental tests.